The range of application of self-management in the northern sector schools in Najran city in the light of digital transformation and the problems of activating it from standpoint of related principals and teachers - Al-Salaia, Jaber Nasser Monaser (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the degree of application of self-management in public education schools in the northern sector of Najran city in the light of digital transformation from the point of view of its principals and teachers, according to the study variables: (gender, years of experience, educational qualification, college, job, sector). The survey descriptive approach, and the tool was represented by distributing a questionnaire that consisted of (38) items distributed over (8) fields; It was applied to an intentional sample of (1195) male and female teachers in (46) schools; All schools in the northern sector of the city of Najran are represented. The results revealed that the degree of application of the Autonomous Administration in the northern sector of the city of Najran has obtained an overall average of (3.42 out of 5), i.e., at the level of the domains; The field of follow-up and accounting got the highest average (3.83), then the field of student performance with an average of (3.74), thirdly, the field of participation in decision-making with an average of (3.60), all with a verbal assessment of the reality of the application with a degree (significant), while fourthly the field of delegation of powers with an average of (3.35) and fifth the field of growth Professional with an average of (3.32), sixth in administrative and financial obstacles with an average of (3.20), seventh in the field of human obstacles with an average of (3.18), eighth and finally, in relationship with the local community with an average of (3.10) and all the last five at a (medium) degree. The results also showed that there are statistically significant differences for all variables. The study: as follows (gender, in favor of females, and according to the variable of years of experience in favor of less than 5 years, and according to the variable of academic qualification in favor of a bachelor’s degree, and according to the variable of college specialization in favor of humanity, and according to the variable of employment in favor of a teacher,) and based on the results, the researcher made a set of recommendations And the proposals to activate the application of self-management in public education schools in the northern sector of the city of Najran in the light of digital transformation and throughout the schools of the Kingdom, and therefore the study recommends the need to develop a clear administrative methodology that will Granting public schools the right to self-manage them in light of public administrative decentralization that outlines educational goals.